An electrochemical sensor for nitrite using a glassy carbon electrode modified with Cu/CBSA nanoflower networks. Issue 39 (20th September 2019) - Sun, Chengxiang; Pan, Wenxia; Zheng, Dianyuan; Zheng, Yuhang; Zhu, Jianhong
Abstract : Flower-like metallic nanocrystals are generally used for applications in analytical science, but so far there have been few reports of 'nanoflowers' made of protein components. Abstract : Flower-like metallic nanocrystals are generally used for applications in analytical science, but so far there have been few reports of 'nanoflowers' made of protein components. Herein, we report a novel electrochemical sensor based on copper ions–crosslinked bovine serum albumin nanoflower networks (Cu/CBSA NFNs). Due to the positive synergistic effects between the protein and copper ions, the new modified GCE delivers enhanced catalytic activity toward the electro-oxidation of nitrite ions. Through differential pulse voltammetry (DPV) the fabricated sensor is found to exhibit good analytical performance. Features include a wide dynamic linear range (0.5 to 500 μM, R 2 = 0.999), a highly reproducible response (R.S.D. of 2.47%), and a low detection limit (0.1 μM, S/N = 3). Furthermore, the versatility of the proposed GCE can be demonstrated by the distinguished selectivity in the presence of some interfering agents and the electrode can also be utilized to determine nitrite in mineral water samples.